Comparative Study of Various Preparation Methods of CuO–CeO2 Catalysts for Oxidation of n–Hexane and iso–Octane - A. Mishra; B. D. Tripathi; A. K. Rai; R. Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
The complete oxidation of n-Hexane and iso-Octane was studied individually in a fixed bed tubular flow reactor over CuO-CeO2 catalysts synthesized via four different methods namely urea-nitrate combustion method, urea gelation/co-precipitation method, citric acid sol-gel method and co-impregnation method. Laser diffraction was employed in catalysts characterization. The results obtained from the complete conversion of n-Hexane and iso-Octane revealed that the CuO-CeO2 catalysts prepared by urea-nitrate combustion method (UNC) showed the best performance than the catalysts prepared by other methods used in the present investigation. CuO-CeO2 catalysts prepared by UNC method achieve total n-Hexane and iso-Octane conversion to CO2 at lower temperatures of 280 0C and 340 0C respectively due to the larger surface area of the catalysts which increases the specific rate of reaction. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)